PE‐CVD of Hydrophilic‐COOH Functionalized Coatings on Electrolyte Gated Field‐Effect Transistor Electronic Layers. Issue 2 (28th September 2012) - Magliulo, Maria; Pistillo, Bianca Rita; Mulla, Mohammad Yusuf; Cotrone, Serafina; Ditaranto, Nicoletta; Cioffi, Nicola; Favia, Pietro; Torsi, Luisa
Abstract A plasma deposition (PE‐CVD) process is proposed to functionalize the surface of P3HT organic semiconductor with an hydrophilic coating characterized by carboxyl groups. The functionalized P3HT is employed as electronic active layer in an electrolyte gated organic field‐effect transistor (EGOFET). Nanometric coatings were plasma deposited at the surface of P3HT from glow discharges fed with ethylene and acrylic acid vapors. The surface chemical composition of coated P3HT along with its wettability, have been assessed by means of X‐ray photoelectron spectroscopy and water contact angle. Results show that PE‐CVD is a valid approach to functionalize P3HT surfaces with carboxyl groups, leaving negligible adverse effect on the EGOFET performances. Possibly, chemical or biological species could be immobilized on PE‐CVD‐functionalized EGOFETs, opening to further developments in their use as sensors. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>